Goldie Montana in a fringed dress - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows Goldie Montana wearing a short fringed dress with shiny thin straps, both of which have slipped off of her shoulders. She has her back to the crowd she is entertaining.